Theoretical aspects of computing - ICTAC 2017 : 14th International Colloquium, Hanoi, Vietnam, October 23-27, 2017, proceedings /: 14th International Colloquium, Hanoi, Vietnam, October 23-27, 2017, proceedings. (2017) - Unknown
No abstract available